The Arabic Hermes : from pagan sage to prophet of science - Van Bladel, Kevin Thomas (Oxford studies in late antiquity, 2009)
This is the first major study devoted to the early Arabic reception and adaption of the figure of Hermes Trismegistus, the legendary Egyptian sage to whom were ascribed numerous works on astrology, alchemy, talismans, medicine, and philosophy.